2021
DOI: 10.1111/pere.12403
|View full text |Cite
|
Sign up to set email alerts
|

Rejection sensitivity and mental well‐being: The positive role of friendship quality

Abstract: Previous research shows a link between rejection sensitivity (RS) and various psychological disorders; however, its relation to the positive psychological construct of mental well-being remains unstudied. This study investigates the relationship between RS and mental well-being while taking the role of friendship quality into consideration for 323 emerging adults using decision tree analysis. In training (R 2 = .29) and test trees (R 2 = .18), RS had the strongest relationship with mental well-being where thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…Specifically, internet addiction among adolescents with high rejection sensitivity decreased with increased school engagement (Li et al, 2021). Similarly, a prior study has also found that the quality of friendship mitigates the detrimental effect of rejection sensitivity on mental well-being (Efeoglu & Sen, 2022). Based on theoretical and empirical evidence, it might be logical to predict that school climate can mitigate the association between rejection sensitivity and aggression.…”
Section: School Climate As a Moderatormentioning
confidence: 94%
“…Specifically, internet addiction among adolescents with high rejection sensitivity decreased with increased school engagement (Li et al, 2021). Similarly, a prior study has also found that the quality of friendship mitigates the detrimental effect of rejection sensitivity on mental well-being (Efeoglu & Sen, 2022). Based on theoretical and empirical evidence, it might be logical to predict that school climate can mitigate the association between rejection sensitivity and aggression.…”
Section: School Climate As a Moderatormentioning
confidence: 94%
“…Beyond the importance of having friends, the benefits of friendship quality on health outcomes have also been documented (Efeoglu & Sen, 2022; Holt-Lunstad et al, 2007). Though positive friend relations yield health benefits (Blieszner et al, 2019; Holt-Lunstad, 2017; Larsen et al, 2014), negative aspects of friendship may produce distinct health benefits as well (Antonucci et al, 2010).…”
Section: Friend Relationships Influence On Health Over Timementioning
confidence: 99%